2020
DOI: 10.1002/csc2.20195
|View full text |Cite
|
Sign up to set email alerts
|

Combining ability of extra‐early biofortified maize inbreds underStrigainfestation and low soil nitrogen

Abstract: Striga hermonthica (Del.) Benth parasitism, low soil N, and nutritional deficiencies of normal-endosperm maize (Zea mays L.) threaten maize yield and exacerbate nutritional problems in sub-Sahara Africa (SSA). This study was conducted (a) to evaluate genetic variation among extra-early maturing maize hybrids with provitamin A and quality protein characteristics, (b) to investigate gene action governing the inheritance of Striga resistance, grain yield, low N tolerance, and other measured traits under low-N, hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 40 publications
8
20
1
Order By: Relevance
“…The results of the present study agreed with those of other researchers(Ifie All rights reserved. 21 maternal effects for GY under contrasting environments but contradicted the findings ofOyekale et al (2020) who reported significant maternal effects for GY under LN, Striga and HN conditions.The significant GCA-male x Env, GCA-female x Env and SCA x Env interactions for GY under the different management conditions suggested that the combining ability of the parents varied across LN, Striga and HN conditions. The result inferred that the additive and non-additive gene effects interacted with the environments in their expression, which justified the importance of multilocation testing in breeding LN tolerant and Striga resistant/tolerant hybrids.…”
mentioning
confidence: 54%
See 3 more Smart Citations
“…The results of the present study agreed with those of other researchers(Ifie All rights reserved. 21 maternal effects for GY under contrasting environments but contradicted the findings ofOyekale et al (2020) who reported significant maternal effects for GY under LN, Striga and HN conditions.The significant GCA-male x Env, GCA-female x Env and SCA x Env interactions for GY under the different management conditions suggested that the combining ability of the parents varied across LN, Striga and HN conditions. The result inferred that the additive and non-additive gene effects interacted with the environments in their expression, which justified the importance of multilocation testing in breeding LN tolerant and Striga resistant/tolerant hybrids.…”
mentioning
confidence: 54%
“…While Ertiro et al (2017), Obeng-Bio et al (2019) and Oyekale et al (2020) reported the inheritance of grain yield under LN to be largely influenced by additive gene action, Badu-Apraku et al (2016), Mafouasson et al (2017) and Annor et al (2019) reported prominence of non-additive genes. Under Striga, Badu-Apraku et al (2020) and Oyekale et al (2020) established that additive gene effects played a greater role in the inheritance of grain yield, Striga damage syndrome rating and Striga emergence while Badu-Apraku et al (2016) documented superiority of non-additive gene effects. Maternal effects were reported to influence the inheritance of grain yield and few traits under LN, Striga and HN conditions by Oyekale et al (2020) while Ifie et al (2015) reported non-significant maternal effects under similar growing conditions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The total potassium (K), phosphorus (P) and nitrogen (N) contents of the soils were determined by Kjeldahl digestion and colorimetric method [41]. The soil analyses at Ile-Ife and Mokwa used in this study are the same as reported by [42]. Following the soil test, the total N available in the high-and low-N plots were augmented with urea to 90 and 30 kg N ha −1 , respectively.…”
Section: Research Locations Experimental Design and Field Managementmentioning
confidence: 99%